Antenatal care and its association with pregnancy outcomes at tertiary care hospital, Jhalawar - Deepender; Shukla, Uma Shankar; Sharma, Anubhav; Gupta, Pankaj Kumar; Jain, Mayank; Saini, Vinod Kumar; Qureshi, Asif (International Journal Of Community Medicine And Public Health, 2023)
Background: Low birth weight is a major public health problem in India. Amongst several many factors affecting birth weight, the two factors are demographic characteristics of mothers and utilization of antenatal care services after timely registration of pregnancy. Aims were to access ANC and its association with pregnancy outcomes at Jhalawar medical college, Jhalawar Rajasthan. Methods: All the pregnant women were admitted to the maternity ward for delivery in November 2022. The interview consisted of a demographic characteristic of mothers, utilization of ANC services, live birth weight of the baby, and records of the mother from the hospital. Data collection was done from the maternity ward and vaccination site. It was a hospital-based cross-sectional study. Results: Among mothers who registered in 1st trimester, 81.6% delivered at full term, 77% of new-born were normal birth weight and only 8.5% of new-born needed NICU admission; compared to those who registered in 2nd and 3rd trimesters delivered at full term 67.1% and 55% respectively, 63.3% and 50% new-born had normal birth weight and NICU admission needed by 17.7% and 55% new-born needed NICU admission respectively. Those mothers who received ≥4 ANC visits had delivered 186 (78.8%) new-born with normal birth weight and required NICU admission for 24 (10.2%) new-born as compared to those who had <4 ANC visits delivered 109 (64.9.8%) new-born with normal birth weight. Conclusions: Early registration of pregnancy prevents chances of LBW baby, long stay in NICU also leads to a reduction in preterm delivery.